CoP-Vp nanocube composite material and preparation method and application thereof
By designing CoP-Vp nanocube composite materials, using the nanocube structure and electronic structure adjustment of phosphorus vacancy Vp, the existing non-precious metal catalysts are solved inadequate performance in electrolytic water hydrogen production system, and an efficient and durable catalytic effect is achieved.
Patent Information
- Application Number
- CN202411860888.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
AI Technical Summary
Existing non-precious metal catalysts are difficult to compare with precious metal catalysts in electrolytic water hydrogen production systems, which limits their commercial development.
A CoP-Vp nanocube composite material is designed to enhance the conductivity and catalytic activity of the composite material by distributing CoP nanoparticles inside and on the surface of the nanocube, and adjusting the electronic structure of CoP through phosphorus vacancy Vp.
By increasing the specific surface area and porous structure of the composite material, more hydrogen evolution active sites are exposed, the adsorption and diffusion capacity of hydrogen ions is improved, and catalytic activity and durability are significantly improved.
Smart Images

Figure CN119877012A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a CoP-V p Nanocube composite material and preparation method and application thereof. Background Art
[0002] Catalysts are the core part of the water electrolysis hydrogen production system, and play an important role in improving the efficiency of electrolysis hydrogen production, reducing the energy consumption of hydrogen production, and ensuring the stable operation of the electrolyzer. At present, most of the water electrolysis catalysts used in practical applications are expensive precious metal catalysts such as platinum carbon electrodes. Although they have high catalytic performance and strong stability, their high cost also limits their development. Therefore, the development and use of non-precious metal catalysts to replace expensive precious metal catalysts is the key to solving PEM technology and realizing large-scale water electrolysis hydrogen production.
[0003] Among them, transition metal phosphides among non-precious metals are the main ideal alternative materials for precious metal catalysts due to their abundant reserves, low prices, unique crystal structures, excellent electrical conductivity and good chemical stability, and have shown excellent electrochemical activity in the electrochemical hydrogen evolution reaction. However, due to the intrinsic catalytic activity of single transition metal phosphide materials, the performance of non-precious metal catalysts is still difficult to match that of precious metal catalysts, which in turn limits their commercial development. Therefore, it is of great significance to design a high-performance, low-cost and simple preparation method transition metal phosphide catalyst. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects in the prior art, thereby providing a CoP-V p Nanocube composite material and preparation method and application thereof.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A CoP-V p A nanocube composite material comprises CoP and a nanocube, wherein the CoP is nanoparticles distributed inside and on the surface of the nanocube, and the crystal of the CoP has a phosphorus vacancy V p .
[0007] Furthermore, the nanocube comprises amorphous carbon, and the amorphous carbon is doped with N and P.
[0008] In order to achieve the above object, the present invention also adopts the following technical solutions:
[0009] A method for preparing the CoP-V p The method for preparing the nanocube composite material comprises the following steps:
[0010] Step S1, preparing ZIF-67 nanocubes and N, P-containing cross-linked composites respectively, mixing the ZIF-67 nanocubes and the N, P-containing cross-linked composites according to a first set ratio, and then grinding and annealing in sequence to obtain a CoP nanocube composite material;
[0011] Step S2: mixing the CoP nanocube composite material with the reducing solution according to a second set ratio, and then performing solid-liquid separation and drying in sequence after mixing evenly to obtain CoP-V p Nanocube composites.
[0012] Furthermore, the reducing solution is a NaBH4 solution.
[0013] Furthermore, the concentration of the reducing solution is 0.2M.
[0014] Further, the second set ratio is a mass ratio of CoP to NaBH4 equal to 1:4-1:6; and / or
[0015] The first set ratio is a mass ratio of the ZIF-67 nanocube to the N and P-containing cross-linked complex of 1:1.3-1:1.75.
[0016] Furthermore, the method further comprises the steps of preparing the ZIF-67 nanocubes:
[0017] Dispersing 2-methylimidazole in deionized water and stirring evenly to obtain a 2-methylimidazole solution;
[0018] Dispersing CTAB in deionized water, adding a cobalt source, and mixing well to obtain a cobalt source solution;
[0019] The cobalt source solution and the 2-methylimidazole solution are uniformly mixed and then subjected to solid-liquid separation and drying in sequence to obtain the ZIF-67 nanocube.
[0020] Furthermore, the method further comprises the steps of preparing the N and P-containing cross-linked composite:
[0021] The phosphorus source solution is added to the nitrogen source solution and mixed evenly, and then filtered, washed, dried and ground in sequence to obtain the N and P-containing cross-linked composite.
[0022] Further, the nitrogen source solution is any one of a melamine solution and a urea solution;
[0023] The phosphorus source solution is a phytic acid solution.
[0024] To achieve the above object, the present invention adopts the following technical solutions:
[0025] A CoP-V pApplication of nanocube composite materials as electrode catalysts for hydrogen evolution in water electrolysis.
[0026] In summary, compared with the prior art, the present invention has at least the following beneficial effects:
[0027] The present invention relates to a CoP-V p Nanocube composite material and preparation method and application thereof, including CoP and nanocube, wherein the CoP is nanoparticles distributed inside and on the surface of the nanocube, making the surface of the formed composite material rougher and increasing the porous structure, thereby increasing the specific surface area of the composite material, greatly exposing the hydrogen evolution active site, providing abundant paths for the rapid transmission of charges, and facilitating the adsorption of hydrogen ions on the CoP-V p The surface of the electrocatalytic material prepared from the nanocube composite material provides diffusion space for hydrogen ions; and the CoP crystal has phosphorus vacancies V p , through the phosphorus vacancy V p Adjusting the electronic structure of the CoP improves the conductivity of the composite material. Furthermore, the phosphorus vacancy V p The presence of reduces the activation energy of the reaction, effectively accelerates the kinetics of the catalytic reaction, and can also serve as an active adsorption site to increase the CoP-V p Catalytic activity and durability of nanocube composites. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 The X-ray diffraction patterns of Example 1 and Comparative Example 1 provided by the present invention.
[0030] Figure 2 This is a high-resolution X-ray photoelectron spectrum of Example 1 and Comparative Example 1 provided by the present invention.
[0031] Figure 3 The atomic ratio diagram of Example 1 and Comparative Example 1 provided by the present invention is obtained by inductively coupled plasma-mass spectrometry.
[0032] Figure 4 This is a scanning electron microscope image of Example 1 provided by the present invention.
[0033] Figure 5 This is a scanning electron microscope image of Comparative Example 1 provided by the present invention.
[0034] Figure 6 This is a comparison chart of the specific surface areas of Example 1 and Comparative Example 1 provided by the present invention.
[0035] Figure 7 This is a comparison chart of pore size distribution of Example 1 and Comparative Example 1 provided by the present invention.
[0036] Figure 8 This is a comparison diagram of the LSV curves of Example 1 and Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0039] A CoP-V p Nanocube composite material, including CoP and nanocube, CoP is nanoparticles distributed inside and on the surface of the nanocube, and the crystal of CoP has phosphorus vacancy V p .
[0040] Specifically, CoP is nanoparticles distributed inside and on the surface of nanocubes, so that the formed CoP-V p The surface of the nanocube composite material is rougher and has a more porous structure, which increases the specific surface area of the composite material. Therefore, a large number of hydrogen evolution active sites are exposed, providing abundant pathways for the rapid transfer of charges, which is conducive to the adsorption of hydrogen ions on the CoP-V p The surface of the electrocatalytic material prepared from the nanocube composite material provides diffusion space for hydrogen ions, ensuring the smooth movement of hydrogen ions, greatly promoting the rapid movement of charges. In addition, since the P-Co bond of the CoP crystal is destroyed during the preparation process, a large number of phosphorus vacancies V are constructed in the CoP crystal. p , from the electronic structure level, the phosphorus vacancy V pThe presence of ions causes the local electron cloud structure to change, which changes the electron state density inside the material, thereby optimizing the channel and efficiency of electron transmission. There is local electron transfer to phosphorus vacancies, which eventually presents an electron-rich state, making CoP-V p The conductivity of the nanocube composite material was enhanced; further, from the perspective of catalysis, the phosphorus vacancy V p The presence of V reduces the activation energy required for the catalytic reaction, effectively accelerating the kinetics of the catalytic reaction. p It can also serve as an active adsorption site to increase CoP-V p The catalytic activity and durability of the nanocube composite material enable the entire catalytic system to operate continuously and efficiently.
[0041] In some embodiments of the present invention, the nanocubes include amorphous carbon, and the amorphous carbon is doped with N and P.
[0042] Specifically, CoP nanoparticles and amorphous carbon jointly maintain the morphology of nanocubes, wherein the amorphous carbon is doped with N atoms and P atoms, which maximizes the conductivity of the composite material, greatly promotes charge transfer at the interface, and is beneficial to the improvement of hydrogen evolution performance.
[0043] In certain embodiments of the present invention, the nanocubes have a size of 400-600 nm.
[0044] In addition to the above CoP-V p The present invention also provides a nanocube composite material that can be used to prepare the above-mentioned CoP-V p Preparation method of nanocube composite material, the CoP-V p Nanocube composite material preparation method and the above CoP-V p Nanocube composites can be referenced against each other.
[0045] A method for preparing CoP-V p The method for preparing the nanocube composite material comprises the following steps:
[0046] Step S1, respectively preparing ZIF-67 nanocubes and N, P-containing cross-linked composites, mixing the ZIF-67 nanocubes and the N, P-containing cross-linked composites according to a first set ratio, and then grinding and annealing in sequence to obtain a CoP nanocube composite material.
[0047] Specifically, the mixture of the two is annealed at high temperature, and ZIF-67 is carbonized to form amorphous carbon after high temperature annealing, and the cross-linked composite containing N and P decomposes, and the generated N atoms and P atoms are doped in the amorphous carbon. Secondly, the Co and P elements contained in the ZIF-67 nanocubes and the cross-linked composite containing N and P generate CoP nanoparticles, and the CoP nanoparticles and amorphous carbon together maintain the morphology of the nanocubes.
[0048] In certain embodiments of the present invention, the first set ratio is a mass ratio of ZIF-67 nanocubes to N, P-containing cross-linked complexes equal to 1:1.3-1:1.75. Preferably, the first set ratio is 1:1.5.
[0049] In some embodiments of the present invention, the annealing condition is to heat the temperature to 850-950° C. at a heating rate of 3-5° C. / min and then anneal for 2 hours. Preferably, the temperature is heated to 900° C. at a heating rate of 5° C. / min.
[0050] In some embodiments of the present invention, annealing is performed in any one of argon, nitrogen and nitrogen-argon mixed gas atmospheres, which is not limited herein. Preferably, annealing is performed in an argon atmosphere.
[0051] Wherein, step S1 also includes the preparation step of ZIF-67 nanocubes:
[0052] Dispersing 2-methylimidazole completely in deionized water and stirring evenly to obtain a 2-methylimidazole solution;
[0053] Dispersing CTAB in deionized water, adding a cobalt source, and mixing well to obtain a cobalt source solution;
[0054] The cobalt source solution is quickly poured into the 2-methylimidazole solution, mixed at a speed of 500-1000 rpm / min, stirred evenly, and then subjected to solid-liquid separation and drying in sequence to obtain ZIF-67 nanocubes.
[0055] In certain embodiments of the present invention, the cobalt source is preferably Co(NO3)·6H2O.
[0056] In certain embodiments of the present invention, the solid-liquid separation method may be centrifugation or filtration, which is not limited here. Preferably, the solid-liquid separation method is centrifugation.
[0057] Furthermore, step S1 also includes a step of preparing a cross-linked composite containing N and P: adding a phosphorus source solution to a nitrogen source solution and mixing the mixture evenly, followed by filtering, washing, drying and grinding to obtain a cross-linked composite containing N and P.
[0058] In certain embodiments of the present invention, the nitrogen source solution is any one of a melamine solution and a urea solution, and the phosphorus source solution is a phytic acid solution.
[0059] In certain embodiments of the present invention, the mass ratio of the nitrogen source to the phosphorus source in the nitrogen source solution and the phosphorus source solution is 0.4:1-0.8:1.
[0060] Step S2: Mix the CoP nanocube composite material and the reducing solution according to a second set ratio, and after mixing evenly, perform solid-liquid separation and drying in sequence to obtain CoP-V p Nanocube composites.
[0061] Specifically, after reduction by a reducing solution, the target product CoP-Vp having P vacancies is formed in the CoP nanocube composite material.
[0062] In certain embodiments of the present invention, the reducing solution is a NaBH4 solution.
[0063] In certain embodiments of the present invention, the concentration of the reducing solution is 0.15-0.25M, preferably 0.2M.
[0064] In certain embodiments of the present invention, the second set ratio is a mass ratio of CoP to NaBH4 of 1:4-1:6. Preferably, the second set ratio is 4:19.
[0065] In certain embodiments of the present invention, the solid-liquid separation method may be centrifugation or filtration, which is not limited here. Preferably, the solid-liquid separation method is centrifugation.
[0066] In certain embodiments of the present invention, the solution used in the centrifugation process is preferably deionized water and anhydrous ethanol.
[0067] In addition, the present invention also provides a CoP-V prepared by the above preparation method p The application of nanocube composite materials is specifically used as electrode catalysts for hydrogen evolution in water electrolysis.
[0068] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0069] The reagents and materials used in the following examples are all commercially available.
[0070] Example 1
[0071] Step S1, completely dispersing 9.08g of 2-methylimidazole in 140ml of deionized water and stirring for 20min to obtain a 2-methylimidazole solution; dispersing 0.01g of CTAB in 20ml of deionized water, adding 0.58g of Co(NO3)·6H2O, and ultrasonicating for 10min to obtain a Co(NO3)·6H2O solution; quickly pouring the Co(NO3)·6H2O solution into the 2-methylimidazole solution, stirring at a speed of 600rpm / min for 30min, and then centrifuging with anhydrous ethanol 8 times, and drying at 60°C for 12h to obtain ZIF-67 nanocubes;
[0072] 0.75 g of melamine was dissolved in 300 mL of deionized water and stirred evenly to obtain a melamine solution; 1 ml of 70% phytic acid solution was added to the melamine solution and stirred for 30 minutes, filtered and washed with deionized water, dried and ground to obtain a cross-linked composite containing N and P;
[0073] The ZIF-67 nanocubes and the N and P cross-linked composite were mixed in a mass ratio of 1:1.5, ground for 10 min, heated to 900 °C at a heating rate of 5 °C / min in an argon atmosphere, and annealed for 2 h to obtain a CoP nanocube composite material;
[0074] Step S2: 0.08 g of CoP nanocube composite material was mixed with 50 ml of 0.2 M NaBH4 solution, centrifuged with anhydrous ethanol and deionized water, and dried completely to obtain CoP-V p Nanocube composites.
[0075] Comparative Example 1
[0076] The difference between this comparative example and Example 1 is that only step S1 is performed, that is, only the CoP nanocube composite material without adding phosphorus vacancies is obtained, and the parameters in the operation of step S1 are the same.
[0077] The composite materials prepared in Example 1 and Comparative Example 1 are marked as Example 1 and Comparative Example 1, respectively. Then, Example 1 and Comparative Example 1 are tested, and the specific test results are analyzed as follows:
[0078] (1) XRD analysis: as attached Figure 1 As shown, compared with the CoP nanocube composite material, CoP-V p The sharpness of the diffraction peak of the nanocube composite material changed, indicating that due to the strong reducing property of sodium borohydride, the crystal structure of Example 1 was destroyed during the reaction, the degree of crystallization became worse, and the defects increased, proving that vacancies were successfully introduced.
[0079] (2) XPS analysis: Figure 2The P 2p high-resolution X-ray photoelectron spectra of the comparative example and the embodiment are shown. It can be seen that the peaks of P 2p 3 / 2 and P 2p 1 / 2 in comparative example 1 are located at 129.7 eV and 130.6 eV, respectively, while the peaks of P 2p3 / 2 and P 2p 1 / 2 in embodiment 1 are located at 129.4 eV and 130.3 eV. By comparison, both peaks of embodiment 1 move toward the low binding energy direction, confirming the generation of phosphorus vacancies.
[0080] (3) Atomic ratio analysis: as shown in the attached Figure 3 As shown in Figure 2, the atomic ratio diagram was obtained by inductively coupled plasma-mass spectrometry. The atomic ratio of P to Co in the CoP nanocube composite material was 1.02, while that of CoP-V p The atomic ratio of P to Co in the nanocube composite is 0.93, which proves that the P atoms are reduced and phosphorus vacancies are generated after the treatment with sodium borohydride solution.
[0081] (4) Microstructure analysis: as shown in the attached Figure 4 As shown in the figure, CoP nanoparticles are evenly distributed on the surface and inside of amorphous carbon. After being corroded by NaBH4, they can still maintain the cubic morphology. The size of the nanocube is 400-600nm. At the same time, due to the strong reducing property of NaBH4, it also affects the structure of the cube, making its porous structure more porous and the surface rougher. Figure 5 As shown, the CoP nanoparticles are uniformly distributed on the surface and inside of the amorphous carbon, and the nanocube size is 400-600nm, but the surface of the CoP nanoparticles is smooth.
[0082] (5) Specific surface area test: as shown in the attached Figure 6 As shown, CoP-V p The specific surface area of the nanocube composite material is 168.4 m 2 / g, compared with the specific surface area of 72.8m 2 / g, the specific surface area is significantly increased. Figure 7 As shown, CoP-V p The pore size distribution of the nanocube composite material is 1.5nm, compared with the pore size distribution of the CoP nanocube composite material between 1-2nm, and the porous structure has increased. Due to the introduction of P vacancies after the corrosion of NaBH4, the surface is rougher, the porous structure is increased, and the specific surface area is increased, which can greatly expose the hydrogen evolution active sites of the surface catalyst, provide abundant paths for the rapid transmission of charges, and facilitate the adsorption of hydrogen ions on the CoP-V p The surface of the electrocatalytic material made of nanocube composite materials effectively provides diffusion space for hydrogen ions.
[0083] (6) Electrochemical test: Shanghai Chenhua electrochemical workstation (CHI-660E) was used, and a three-electrode system was selected, with glassy carbon electrode, graphite and Ag / AgC1 as working electrode, counter electrode and reference electrode respectively. The electrolyte was a freshly prepared 0.5MH2SO4 solution, and the test temperature was room temperature.
[0084] Preparation of working electrode: 4 mg of catalyst sample was weighed and dispersed in 1 mL of a mixed solution of water and alcohol (V water: V alcohol = 3:2). Subsequently, 30 μL of Nafion (0.5 wt%) solution was added and ultrasonicated for 1 h to form a uniform slurry. Then, 5 μL of the sample was pipetted and dropped on the glassy carbon electrode surface (catalyst loading was 0.28 mg cm -2 ). After it is completely dry, it can be used for electrochemical testing.
[0085] As attached Figure 8 As shown, CoP-V p The catalytic activity of the nanocube composite material is higher than that of the CoP nanocube composite material. -2 When the overpotential of CoP nanocube composite material is 163mV, while CoP-V p The overpotential of the nanocube composite material is 133 mV. It can be seen that the introduction of crystal vacancies can improve the conductivity by adjusting the electronic structure, thereby adding more active sites and ultimately improving the catalytic activity.
[0086] In summary, combined with the results of each test, CoP-V p Due to the introduction of P vacancies, the nanocube composite material exhibits the characteristics of a rougher surface, more porous structure and larger specific surface area. Therefore, it can greatly expose the hydrogen evolution active sites of the surface catalyst, provide diffusion space for hydrogen ions, and further enhance the conductivity, effectively improving the catalytic activity.
[0087] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A CoP-V p Nanocubic electrode catalyst, characterized in that The invention comprises CoP and a nanocube, wherein the CoP is nanoparticles distributed inside and on the surface of the nanocube, and the crystal of the CoP has a phosphorus vacancy V p .
2. The CoP-V according to claim 1 p Nanocube composite material, characterized in that The nanocubes include amorphous carbon, and the amorphous carbon is doped with N and P.
3. A method for preparing the CoP-V according to claim 1 or 2 p A method for preparing a nanocube composite material, characterized in that: The following steps are involved: Step S1, preparing ZIF-67 nanocubes and N, P-containing cross-linked composites respectively, mixing the ZIF-67 nanocubes and the N, P-containing cross-linked composites according to a first set ratio, and then grinding and annealing in sequence to obtain a CoP nanocube composite material; Step S2: mixing the CoP nanocube composite material with the reducing solution according to a second set ratio, and then performing solid-liquid separation and drying in sequence after mixing evenly to obtain CoP-V p Nanocube composites.
4. The CoP-V according to claim 3 p A method for preparing a nanocube composite material, characterized in that: The reducing solution is NaBH4 solution.
5. The CoP-V according to claim 4 p A method for preparing a nanocube composite material, characterized in that: The concentration of the reducing solution is 0.2M.
6. The CoP-V according to claim 3 p A method for preparing a nanocube composite material, characterized in that: The second set ratio is a mass ratio of CoP to NaBH4 equal to 1:4-1:6; and / or The first set ratio is a mass ratio of the ZIF-67 nanocube to the N and P-containing cross-linked complex of 1:1.3-1:1.
75.
7. The CoP-V according to claim 3 p A method for preparing a nanocube composite material, characterized in that: The preparation steps of the ZIF-67 nanocubes are also included: Dispersing 2-methylimidazole in deionized water and stirring evenly to obtain a 2-methylimidazole solution; Dispersing CTAB in deionized water, adding a cobalt source, and mixing well to obtain a cobalt source solution; The cobalt source solution and the 2-methylimidazole solution are uniformly mixed and then subjected to solid-liquid separation and drying in sequence to obtain the ZIF-67 nanocube.
8. The CoP-V according to claim 3 p A method for preparing a nanocube composite material, characterized in that: The method also includes the steps of preparing the N and P-containing cross-linked composite: The phosphorus source solution is added to the nitrogen source solution and mixed evenly, and then filtered, washed, dried and ground in sequence to obtain the N and P-containing cross-linked composite.
9. The CoP-V according to claim 8 p A method for preparing a nanocube composite material, characterized in that: The nitrogen source solution is any one of a melamine solution and a urea solution; The phosphorus source solution is a phytic acid solution.
10. A CoP-V as claimed in claim 1 p Application of nanocube composite material, characterized in that, Electrode catalyst used in water electrolysis for hydrogen evolution.